Fenomena Solidaritas Sosial Melalui Media Sosial Saat Pandemi Covid-19 (Studi Kasus Pada Konser Musik #dirumahaja oleh Narasi TV) - Nabila Nur Farida; Yolanda Presiana Desi (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
This research is motivated by various social solidarity actions both offline and online that happen a lot in the community during the Covid-19 pandemic. This qualitative research method aims to get an overview of the phenomenon of social solidarity through social media conducted by Narasi TV through the Music Concert #dirumahaja Fighting Corona Solidarity. The theory used is the theory of social capital which consists of trust, reciprocity, social interaction and elements of social media 4C those are context, communication, collaboration and connection. Primary data sources were gained through observations on Instagram @narasi.tv and interviews with 5 followers of @narasi.tv who took part in the #dirumahaja Corona Fighting Solidarity Music Concert and made donations. Meanwhile, secondary data sources were gained through questionnaires to 50 followers of @narasi.tv. The results show that trust, reciprocity and social interaction as well as elements of social media 4C context, communication, collaboration and connection play an important role in increasing social solidarity through social media. The use of verified social media accounts and trusted online donation platforms as well as the involvement of well-known figures and the right communication strategies have made the #dirumahaja Corona Fighting Solidarity Music Concert became the pioneer in social solidarity actions through live streaming music concerts on social media.